A Semi-Analytical Model for Separating Diffuse and Direct Solar Radiation Components - Eugenia Paulescu; Marius Paulescu (Applied Sciences, 2022)
The knowledge of the solar irradiation components is required by most solar applications. When only the global horizontal irradiance is measured, this one is typically broken down into its fundamental components, beam and diffuse, by applying an empirical separation model. This study proposes a semi-analytical model for diffuse fraction, defined as the ratio of diffuse to global solar irradiance. Starting from basic knowledge, a general equation for diffuse fraction is derived. Clearness index, relative sunshine, and the clear-sky atmospheric transmittance are highlighted as robust predictors. Thus, the model equation implicitly provides hints for developing accurate empirical separation models. The proposed equation is quasi-universal, allowing for temporal (from 1-min to 1-day) and spatial (site specificity) customization. As a proof of theory, the separation quality is discussed in detail on the basis of radiometric data retrieved from Baseline Surface Radiation Network (BSRN), station Magurele, Romania. For temperate continental climate, overall results show for the diffuse fraction estimation a maximum possible accuracy around 7%, measured in terms of normalized root mean square error. One of the many options of implementing the semi-analytical model is illustrated in a case study.